PENDAPATAN USAHATANI KACANG TANAH DI DESA KANONANG II KECAMATAN KAWANGKOAN - Grace A.J. Rumagit; Oktavianus Porajouw; Rizky Mirah (AGRI-SOSIOEKONOMI, 2011)
The aim of this study is to determine the income of peanut’s farm in The Second Kanonang Villageat Kawangkoan District. Primary and seconndary data are used and analyzed by making use ofdescriptive analysis and R/C ratio. Results of this study indicates that: (1) the average revenue of peanutfarmers is Rp6.053.800 and the average cost of Rp 3.182.577 so that the average income received byfarmers is Rp 2.871.223 per one time of planting, and (2) the R/C ratio (1.90) is greater than one, showedthat the average income received by farmers is relatively favorable.